COLLATERAL DAMAGE: PERLINDUNGAN LINGKUNGAN PADA SAAT KONFLIK BERSENJATA DALAM PERSPEKTIF DEEP ECOLOGY - Kharismawan, Gede Khrisna; I Made Budi Arsika (Faculty of Law, Parahyangan Catholic University, 2022)
International humanitarian law that applies in armed conflict tends to prioritize human interests. The emergence of deep ecology manifests as a critique of the anthropocentrism of war which harms the natural environment. This development implies the need for environmental protection and emphasizes responsibility for environmental damage resulting from armed conflict. This article discusses international legal frameworks that offer protection to the environment in times of armed conflict and presents an analysis of legal protection from a deep ecology perspective. This paper is a normative legal research that applies statutory, case, and conceptual approaches. The study's results suggested that several international treaties have adopted international customs in regulating the protection of the environment during armed conflict and forms of responsibility in case a violation occurs. However, those international legal instruments have yet to be optimal in protecting the environment regarding damage standards, coverage of environmental conditions, and the implementation of responsibility for violations.